HUBUNGAN PENERAPAN ORGANISASI PEMBELAJAR DAN GAYA KEPEMIMPINAN DALAM MEMBINA GURU PEMBELAJAR DENGAN KOMITMEN ORGANISASIONAL GURU - Masturah, Masturah; Asrori, M.; Wahyudi, Wahyudi (STKIP Persada Khatulistiwa Sintang, 2025)
This study aimed to investigate the relationship between the implementation of learning organizations and leadership styles in teacher development with teachers’ organizational commitment. The research employed a quantitative approach with a descriptive method using an interrelationship study design to reveal the correlations between learning organization practices and leadership styles in fostering teacher development with organizational commitment in Siantan District. The sample consisted of 56 elementary school teachers, drawn from the population of all teachers in Siantan. Data were collected through questionnaires and documentation, then analyzed using Pearson’s product-moment correlation. The findings revealed three main results: first, a significant relationship exists between principals’ implementation of learning organizations in teacher development and teachers’ organizational commitment; second, a clear correlation is found between principals’ leadership styles in guiding teacher learning and the level of teachers’ organizational commitment; third, the analysis quantified the strength of these relationships, showing that (a) learning organization implementation contributed 42.64% of the variance in organizational commitment, while 57.36% was influenced by external factors, and (b) leadership style implementation accounted for 35.40% of the variance, with 64.60% due to external factors.